A context-based study of serendipity in information research among Chinese scholars. Issue 3 (14th May 2018) - Zhou, Xiaosong; Sun, Xu; Wang, Qingfeng; Sharples, Sarah
Abstract : Purpose: The current understanding of serendipity is based primarily on studies employing westerners as the participants, and it remains uncertain whether or not this understanding would be pervasive under different cultures, such as in China. In addition, there is not a sufficient systematic investigation of context during the occurrence of serendipity in current studies. The purpose of this paper is to examine the above issues by conducting a follow-up empirical study with a group of Chinese scholars. Design/methodology/approach: The social media application "WeChat" was employed as a research tool. A diary-based study was conducted and 16 participants were required to send to the researchers any cases of serendipity they encountered during a period of two weeks, and this was followed by a post-interview. Findings: Chinese scholars experienced serendipity in line with the three main processes of: encountering unexpectedness, connection-making and recognising the value. An updated context-based serendipity model was constructed, where the role of context during each episode of experiencing serendipity was identified, including the external context (e.g. time, location and status), the social context and the internal context (e.g. precipitating conditions, sagacity/perceptiveness and emotion). Originality/value: The updated context model provides a further understanding of the role played by context during the different processes of serendipity. The framework for experiencing serendipity has been expanded, and this may be used to classify the categories of serendipity.